Assessment and management of coastal erosion in the marine protected area of the Rosario Island archipelago (Colombian Caribbean) (2023)
By utilizing historical satellite image databases, it was possible to assess the rates of coastal retreat in the Grande, Rosario, and Tesoro Islands from 2010 to 2021, due to the influence of climatic variables. It was discovered that the three islands have lost 0.4%, 1.6%, and 9.3% of their landmass, respectively. The notable increase in sea level rise, which has risen 6.2 mm/year since 2010, has emerged as the primary driving factor in the magnitude of erosion by altering the wave transformation patterns in shallow waters. This enables the wave trains to maintain more energy and intensify their height in surf zones, particularly during the dry season, where the wave height has increased by 12%. At the same time, the intensity of longitudinal currents has increased due to the new wave dynamics, leading to changes in the coastlines. Areas characterized by a coastal geomorphology of terraces and beaches, such as Tesoro Island, were found to be the most affected, unlike the cliffs of Grande and Rosario Islands. The study also revealed a lack of policies and concrete actions aimed at mitigating erosion in the coral islands of the Colombian Caribbean. Thus, a set of guidelines is proposed as a starting point to address this issue.